Structured online vivas for evaluating professional competency in a capstone allied health course : A pilot study. - Maranna, Sandhya; Osborne, Brooke; Nallaya, Shashi (Advancing Scholarship and Research in Higher Education v.4 n.1 p.1-21 https://asrhe.org/index.php/asrhe/article/view/7813/6641, 2024)
The aim of this pilot study was to develop structured online vivas as authentic assessments for capstone students enrolled in the medical sonography program in an Australian university. The objective was to evaluate the professional competency of trainee students who were transitioning to graduate as accredited sonographers. Prior to 2020, capstone students, located all over Australia, travelled to South Australia to undertake an on-campus, objective structured clinical examination for practical skills assessment. The interstate travel restrictions imposed by the COVID-19 pandemic resulted in the need for this examination to be conducted in an online mode. The emergency adaptation model employed in 2020 did not assess conceptual understanding and communication skills. To address this gap, structured online vivas were created and implemented through action research with 71 students in November 2021. A response rate of 51% from student feedback and 100% from external examiner feedback helped to enhance future iterations. Structuring of online vivas enabled assessment of professional competency skills, reduced both examiner bias and student anxiety, and promoted academic integrity. Our study discusses the action research process of developing and implementing structured online vivas, student performance, and evaluating student and examiner experiences with online vivas. [Author abstract]